The thelytokous strain of the parasitoid Neochrysocharis formosa outperforms the arrhenotokous strain in reproductive capacity and biological control of agromyzid leafminers. Issue 2 (28th November 2022) - Ye, Fuyu; Yang, Yuemei; Zhang, Yibo; Pan, Liting; Yefremova, Zoya; Yang, Liyan; Guo, Jianyang; Liu, Wanxue
Abstract: BACKGROUND: Both arrhenotoky (sexual reproduction of females and asexual reproduction of males) and thelytoky (asexual reproduction of females) occur within the order Hymenoptera. The existence of both thelytokous and arrhenotokous strains within one species provides an opportunity to compare the biocontrol efficiency between two reproductive modes. The parasitoid Neochrysocharis formosa (Westwood) (Hymenoptera: Eulophidae) has thelytokous and arrhenotokous strains with sympatric distributions. This parasitoid is used to control invasive leafminers through feeding, stinging, and parasitization. To compare the biocontrol efficiency of the two strains, we analyzed life tables and host‐killing parameters of these two strains reared on the leafminer Liriomyza sativae Blanchard using the age‐stage, two‐sex life table and the CONSUME‐MSChart software. RESULTS: Our results showed that the intrinsic rate of increase ( r ), finite rate of increase ( λ ), and net reproduction rate ( R 0 ) of the thelytokous strain were significantly higher than those of the arrhenotokous strain. The thelytokous females also performed better than the arrhenotokous females for the net host‐feeding rate, net host‐stinging rate, and net host‐killing rate, but not the finite parasitism rate. Conclusively, the finite host‐killing rate of the thelytokous strain (0.8720 ± 0.0516) was significantly higher than that of the arrhenotokous strain (0.5914 ± 0.0832). CONCLUSION: We concluded that thelytokous N. formosa is a better candidate as a biocontrol agent than arrhenotokous N. formosa to control leafminers. Our results shed light on how to choose a better biocontrol agent for integrated pest management (IPM) based on biological control, especially for co‐occurring thelytokous and arrhenotokous parasitoids. © 2022 Society of Chemical Industry. Abstract : We comprehensively compared the life table parameters and three host‐killing rates of thelytokous and arrhenotokous Neochrysocharis formosa strains to evaluate their biocontrol potential. Our results indicated that the thelytokous strain of N. formosa could be a better natural enemy for controlling leafminers than its arrhenotokous strain under laboratory conditions.